The Influence of Offering Discounts through Social Media and Service Quality on Customer Loyalty in Laundry Services (A Case Study of KEN'Z Wash House, Tangerang) - Maesaroh Tri Susilowati; Aris Gumilar; Ismayudin Yuliyzar (PT Mattawang Mediatama Solution, 2024)
Laundry in the present era is concurrent with the increasing competition in similar businesses. In terms of advertising and service quality, customers have various options for different laundry services. Consistent marketing and high-quality services will result in satisfied customers. Customers will be more satisfied when a business meets or exceeds their needs. This largely depends on how well the staff members perform their tasks. Therefore, KEN'Z Wash House emphasizes greatly on evaluating the effectiveness of services to customers, determined by customer feedback. By providing surveys for customers to fill out, KEN'Z Wash House hopes to measure the level of customer loyalty. Survey questions have a strong correlation with promotion and the quality of services provided from the perspective of perceived customer loyalty. Findings from these surveys will be analyzed to determine the extent of the impact of price reductions on social media and consistently high-quality services. By understanding how well KEN'Z Wash House services relate to customer loyalty, the company can gain deeper insights into its customers' opinions regarding discounts offered through social media and the quality of services provided by its staff. This will enable the company to develop strategies that effectively enhance future performance and win back loyal customers.